Study on Strengthening Plan of Safety Network CCTV Monitoring by Steganography and User Authentication - Jung-oh Park; Sanggeun Kim (Advances in Multimedia)
Recently, as the utilization of CCTV (closed circuit television) is emerging as an issue, the studies on CCTV are receiving much attention. Accordingly, due to the development of CCTV, CCTV has IP addresses and is connected to network; it is exposed to many threats on the existing web environment. In this paper, steganography is utilized to confirm the Data Masquerading and Data Modification and, in addition, to strengthen the security; the user information is protected based on PKI (public key infrastructure), SN (serial number), and R value (random number) attributed at the time of login and the user authentication protocol to block nonauthorized access of malicious user in network CCTV environment was proposed. This paper should be appropriate for utilization of user infringement-related CCTV where user information protection-related technology is not applied for CCTV in the future.